Friend or foe? The role of SIRT6 on macrophage polarized to M2 subtype in acute kidney injury to chronic kidney disease - Xiaoqin Gao; Xingwei Liu; Zhaodi Han; Hui Liao; Rongshan Li (Renal Failure)
Acute kidney injury (AKI) substantially increases the risk of developing and worsening chronic kidney disease (CKD). The shift from AKI to CKD is a complex process that involves various cell types, with macrophages playing a key role in responding to renal injury. M1 and M2 macrophages—the two main types of macrophages—have distinct functions at various stages. M1 macrophages induce kidney damage by secreting pro-inflammatory cytokines immediately after injury, whereas M2 macrophages subsequently facilitate kidney tissue repair. The conversion of macrophages from the M1 to M2 subtype is vital for effective repair after renal injury. However, when M2 macrophages infiltrate persistently, they can paradoxically cause fibrosis, thereby complicating recovery. As a key epigenetic regulatory factor, the deacetylase SIRT6 exerts various biological effects through its enzymatic reactions, including the regulation of cellular metabolism, antioxidant stress response, and inhibition of fibrosis. SIRT6 is expressed in all major types of renal resident cells and is demonstrated to protect the kidneys. SIRT6 promotes the transition from the M1 to M2 subtype; nevertheless, this process poses the risk of fibrosis if macrophages remain in the M2 subtype because of the influence of SIRT6. This review aimed (i) to delve into the intricate role of SIRT6 in macrophage polarization toward the M2 subtype in the context of the progression from AKI to CKD and (ii) to explore potential strategies that may effectively target and mitigate the progression from AKI to CKD.